A Cell-Based Target Engagement Assay for the Identification of Cereblon E3 Ubiquitin Ligase Ligands and Their Application in HDAC6 Degraders. Issue 7 (16th July 2020) - Yang, Ka; Zhao, Yu; Nie, Xueqing; Wu, Hao; Wang, Bo; Almodovar-Rivera, Chelsi M.; Xie, Haibo; Tang, Weiping
Summary: Proteolysis-targeting chimeras (PROTACs) is a paradigm shift for small-molecule drug discovery. However, limited E3 ubiquitin ligase ligands with cellular activity are available. In vitro binding assays involve the expression and purification of a large amount of proteins and they often yield ligands that are inactive in cell-based assays due to poor cell permeability, stability, and other reasons. Herein, we report the development of a practical and efficient cell-based target engagement assay to evaluate the binding affinity of a small library of cereblon ligands to its E3 ligase in cells. Selected cell-permeable E3 ligase ligands derived from this assay are then used to construct HDAC6 degraders with cellular protein degradation activity. Because the assay does not involve any genetic engineering, it is relatively easy to transfer from one cell type to a different one. Graphical Abstract: Highlights: Cell-based assay developed for evaluating the binding affinity of CRBN E3 ligands A small library of CRBN E3 ligands was synthesized and examined by this assay Selected E3 ligands were used to construct cellular active HDAC6 degraders Abstract : Yang et al. developed a cell-based target engagement assay for the identification of cereblon E3 ubiquitin ligase ligands, whose utility was demonstrated for the degradation of HDAC6. This strategy provides a practical and efficient alternative to the biochemical assay to evaluate the ligands of E3 ubiquitin ligases.